Global symmetry breaking and topological defects - Valenzuela, Mississippi (2023)
In this article, we present the fundamentals of Goldstone's theorem and the breaking of global symmetries. As well as one of the important aspects to take into account in the process of spontaneous symmetry breaking are the possible topological defects generated by the breaking. For this reason, we will expose the concept of topological defect and the calculation of the relic density of the axion, considered as a candidate to dark matter.